FvbHLH9 Functions as a Positive Regulator of Anthocyanin Biosynthesis by Forming a HY5–bHLH9 Transcription Complex in Strawberry Fruits. (4th February 2020) - Li, Yang; Xu, Pengbo; Chen, Guanqun; Wu, Jun; Liu, Zhongchi; Lian, Hongli
Abstract: Anthocyanin accumulation is transcriptionally regulated by the MYB–bHLH–WD40 complex. Light is indispensable for anthocyanin accumulation, and light-inducible MYB and HY5 were considered to promote anthocyanin accumulation in many fruits. Whether and how light-inducible bHLH transcription factor and HY5 regulate anthocyanin synthesis in strawberry is unknown. In this study, we identified a bHLH transcription factor, FvbHLH9, which was induced by light as well as FvHY5, and found that, similar to FvHY5, the transient overexpression and interference FvbHLH9 in strawberry fruits can promote and decrease anthocyanin accumulation, respectively, indicating FvbHLH9 functions as a positive regulator of anthocyanin biosynthesis. Furthermore, we confirmed that both FvHY5 and FvbHLH9 specifically bind to the promoter region of some key enzyme genes, including FvDFR, and the expression of FvDFR was activated through the heterodimer formation between FvHY5 and FvbHLH9. Finally, we confirmed that FvbHLH9-promoted anthocyanin accumulation is dependent on HY5–bHLH heterodimerisation in Arabidopsis. Our findings provide insights into a mechanism involving the synergistic regulation of light-dependent coloration and anthocyanin biosynthesis via a HY5–bHLH heterodimer formed by the interaction of FvHY5 and FvbHLH9 in strawberry fruits.